Surgical Approaches for Orbital Floor Fractures: A Meta-Analysis of Clinical Outcomes and Complication Rates Comparing Transconjunctival, Subciliary, and Endoscopic Techniques - Disa Saraswati; Agus Rudi Asthuta (HM Publisher, 2025)
The optimal surgical pathway for the remediation of orbital floor fractures persists as a topic of considerable deliberation among ophthalmic and maxillofacial surgeons. The primary surgical modalities—transconjunctival, subciliary, and endoscopic techniques—each present a unique profile of advantages and inherent limitations with respect to surgical exposure, aesthetic outcomes, and the incidence of postoperative complications. This meta-analysis was undertaken to conduct a comparative evaluation of the clinical outcomes and complication rates associated with these three principal surgical approaches employed in the repair of orbital floor fractures. A meticulous and systematic search of prominent medical databases, including PubMed, Embase, and the Cochrane Library, was performed to identify relevant comparative studies published between January 2014 and December 2024. These studies were required to evaluate transconjunctival, subciliary, and/or endoscopic techniques for the repair of orbital floor fractures. Data from seven heterogeneous comparative studies were ultimately synthesized for this analysis. The primary outcome measures assessed were the incidence of postoperative persistent diplopia and the occurrence of significant enophthalmos, defined as globe retrodisplacement of 2 mm or greater. Secondary outcomes encompassed a range of complication rates, specifically including infraorbital nerve (ION) hypoesthesia, lower eyelid malpositions such as ectropion and entropion, and postoperative surgical site infections. Pooled odds ratios (ORs) or risk ratios (RRs) with their corresponding 95% confidence intervals (CIs) were calculated, employing a random-effects model to account for inter-study variability. The analysis incorporated seven studies, comprising a total of 850 patients who underwent surgical correction for orbital floor fractures. The distribution of patients across the surgical modalities was as follows: 300 patients were managed via a transconjunctival approach, 350 patients via a subciliary approach, and 200 patients via an endoscopic approach. The findings indicated that the transconjunctival approach was associated with a statistically significant lower rate of postoperative ectropion (OR 0.25, 95% CI 0.10-0.65) when compared to the subciliary approach. No statistically significant differences were observed in the rates of persistent diplopia (Transconjunctival vs. Subciliary: OR 0.90, 95% CI 0.55-1.48; Transconjunctival vs. Endoscopic: OR 1.10, 95% CI 0.60-2.01) or significant enophthalmos among the three surgical groups. Endoscopic approaches demonstrated a trend towards lower rates of new or worsened ION hypoesthesia (OR 0.60, 95% CI 0.30-1.19 vs. combined transcutaneous approaches), although this did not achieve statistical significance. In conclusion, this meta-analysis suggests that the transconjunctival approach may offer a superior lower eyelid cosmetic outcome by substantially reducing the risk of ectropion relative to the subciliary approach. All three evaluated techniques demonstrated comparable efficacy in addressing the primary functional objectives of resolving diplopia and correcting enophthalmos. The selection of an appropriate surgical approach should, therefore, be an individualized decision, meticulously considering surgeon experience and expertise, the specific characteristics and complexity of the fracture, and pertinent patient-related factors and preferences. There remains a compelling need for further high-quality, large-scale randomized controlled trials to definitively establish the potential superiority of one approach over the others across a broader range of outcomes.